2014
DOI: 10.1155/2014/719061
|View full text |Cite
|
Sign up to set email alerts
|

Oral Metastasis of Metaplastic Breast Carcinoma in a Patient with Neurofibromatosis 1

Abstract: Neurofibromatosis type 1 (NF1) has been associated with an increased risk for development of malignancy, especially malignant peripheral nerve sheath tumors. In addition, recently, literature has demonstrated an increased risk of breast cancer in women with NF1. The present paper shows a 53-year-old woman with NF1 who presented with metaplastic breast carcinoma and developed multiple metastases, including mandible. Furthermore, we reviewed the English literature, found 63 cases showing the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…4,34 Several previous studies have identified NF1 mutations in MBC, including germline mutations in patients with neurofibromatosis type 1. 4,10,[35][36][37][38][39][40] Our findings provide further evidence of a role for the NF1 gene in a subset of MBC.…”
Section: Semir Vranic Et Alsupporting
confidence: 58%
“…4,34 Several previous studies have identified NF1 mutations in MBC, including germline mutations in patients with neurofibromatosis type 1. 4,10,[35][36][37][38][39][40] Our findings provide further evidence of a role for the NF1 gene in a subset of MBC.…”
Section: Semir Vranic Et Alsupporting
confidence: 58%
“…While the relationship between NF1 alterations and breast cancer is well known [41][42][43], and indeed with aggressive breast cancers [44], we have presented novel data to support a link between NF1 mutations and the metaplastic subtype, and showed weak heterogeneous expression of NF1 in mutant cases. These data are supported by a series of six recent case reports, each highlighting an ostensibly 'unique' case of metaplastic breast cancer in a neurofibromatosis patient (NF1; inherited mutant NF1 syndrome) [45][46][47][48][49][50]; four out of six cases presented with a squamous phenotype, with the remaining two being spindle. A single sporadic NF1 mutation in MBC was also reported in a squamous tumour, as part of a targeted sequencing assessment of 16 MBCs [51].…”
mentioning
confidence: 59%
“…Only two cases have been reported so far in the English literature. [ 5 6 ] Our case is the third case report of metaplastic breast cancer in an NF1 patient. Since it is difficult to address the association of a particular subtype such as metaplastic breast cancer with NF1 from this single case, further studies on the molecular mechanisms and association of breast cancer, including metaplastic breast cancer, with neurofibromatosis are needed.…”
Section: Discussionmentioning
confidence: 86%
“…[ 4 ] So far, only two cases of metaplastic carcinoma in patients with NF1 have been described in the English literature. [ 5 6 ] We present a case of metaplastic breast cancer with keratinizing squamous histology in a patient with history of NF1. The imaging findings of metaplastic breast carcinoma and the association between metaplastic breast cancer and neurofibromatosis are reviewed and discussed.…”
Section: Introductionmentioning
confidence: 99%